Critical Review of Homo Deus: A Brief History of Tomorrow - Hamed Vahdati Nasab; Alieh Abdollahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The under review book of Homo Deus, A Brief History of Tomorrow, is the second part of the trilogy of Sapiens, Homo Deus, and 21 Lessons for the 21st Century were all written by Yuval Noah Harari. In this book, the writer has first reviewed the history behind the formation of the human mindset from Paleolithic to the renaissance with particular emphasis on the scientific revolution and appearance of the humanism paradigm and its subdivisions (liberalism, socialism, and fascism). Doing so, he concluded that the invention of the internet of everything and using more sophisticated computer-generated algorithms by Google and Facebook (Dataism) would eventually put humans aside forever. The writers of this critique compared the Farsi translation with the English one and realized that some parts of the Farsi version suffer from improper translation, and some other parts have been deleted during the translation. In addition to that, it is probable that human societies might escape from the illustrated dark future by Harari. Learning from past events, and more importantly, using our global consciousness, which we possess more than ever, might change the inevitable future.